Problems of Blended Learning in Teaching German in Higher Education - Mansurova , Gulbakhor Makhdievna (Miasto Przyszłości, 2023)
In the context of rapid development and complexity of technology, the activity of a teacher in developing courses becomes much more complicated and requires the development of special skills and teaching techniques. The article discusses the main points of using the blended learning approach in teaching German, since the concept of blended learning represents a fundamental change in the educational model, combining the advantages of classroom work with the possibilities of technological expansion of active learning in an online environment.